Safety Gear Decontamination Practices Among Florida Firefighters: Analysis of a Text-Based Survey Methodology. (November 2018) - Moore, Kevin J.; Koru-Sengul, Tulay; Alvarez, Armando; Schaefer-Solle, Natasha; Harrison, Tyler R.; Kobetz, Erin N.; Caban-Martinez, Alberto J.
Despite the National Fire Protection Association (NFPA) 1851 Personal Protective Equipment Care and Maintenance guidelines, little is known about the routine cleaning of firefighter bunker gear. In collaboration with a large Florida firefighter union, a mobile phone text survey was administered, which included eight questions in an item logic format. In total, 250 firefighters participated in the survey of which 65% reported cleaning their bunker gear in the past 12 months. Approximately 32% ( n = 52) indicated that they had above average confidence in gear cleaning procedures. Arriving at a fire incident response was a significant predictor of gear cleaning in the 12 months preceding survey administration. Using mobile phone–based texting for periodic queries on adherence to NFPA cleaning guidelines and safety message distribution may assist firefighters to increase decontamination procedure frequency.